Assessment of Bio-Energy Potential in Tea Industries of India - Kumar , Sonu; Pou, K.R Jolvis (Asian Journal of Agriculture and Rural Development, 2016)
Tea production is an energy intensive agro-processing trade. Since high demand of energy and increased in fuel prices, tea waste can be utilized to supplement part of energy required in tea processing. This study was conducted in tea estates of Assam (North Lakhimpur, Sonitpur, and Silchar), India. The total energy consumption in tea manufacturing was found to be 4.2-8.5 kWh/kg of made tea. Thus, total energy consumption (5 kWh/kg of tea) for manufacturing of 1197 million kg of tea from 564 thousand hectare tea plantation in India (during 2014-2015) was 5.985×109 kWh. The total obtainable energy from tea waste was estimated and the conversion efficiency of calorific value to electrical energy was assumed to be 10%, which is the least value of conversion efficiency. Energy potential in processing and garden waste was found to be 11.999×107 kWh and 3.492×1010kWh, respectively, and corresponding electrical energy was estimated to be 1.1999×107 kWh and 3.492×109 kWh, respectively. Thus, comparing the energy that could be generated from wastes in tea estate and that required in tea manufacturing, it can be concluded that the huge amount of energy could be saved with the utilization of tea waste.